Involuntary major changes: student narrative about what helped and hindered their adaptability - Streufert, Billie (Kansas State University, 2023)
Career services professionals and academic advisors support students as they pursue their goals. Yet, scholars know little about the lived experiences of students placed into alternative degree programs after they fail to secure admission or are rescinded from a selective or regulated professional program such as nursing, teaching, or social work. This narrative inquiry study examines the critical events of participants who survived unplanned academic loss included in stories about their undergraduate education. Individual interviews with participants humanized and brought voice to their coping strategies, barriers, career decision-making, and persisting toward graduation. Higher education leaders can use the findings to foster policy revisions, cross-departmental well-being collaboration, and strategic support during individual conversations with students coping with change.
Keywords: Goal disengagement; Career advising; Academic advising; Career counseling; Higher education; Goal reengagement